Determinación de cultivos hospedantes del hongo sclerotium sp al ser inoculados bajo invernadero en la granja Santa Inés - Quezada García, Leidy Patricia (2015)
The present work realized in the Granja “Santa Inés”, of the Universidad Técnica de Machala, in which there determined the cultivation landlords of the mushroom Sclerotium sp., originated from isolations of the cultivation of the tomato and rice, which were inoculated under hothouse with the target to identify the incidence of the mushroom with other possible vegetable species host, by means of the isolation in vitro of Sclerotium sp., cultivated in a way of cultivation PDA (it swallows dextrose agar); they were inoculated in the different plants of short cycle and there were taken into account the esclerotia produced in each of the evaluated cultivation. For the work 10 treatments were realized with two repetitions, to more than one witness for cultivation, taking variables as the percentage of germination, formation of esclerotia in plants inoculated with micelio of Sclerotium sp. originated from isolations of the cultivation of the rice and tomato, to 2, 4, 8 and 12 days after its inoculation, respectively. In accordance with the incidence of the illness, so much for the isolations of the mushroom originated from the cultivation of rice and tomato this one fond you will cultivate nine of 10 studied, that is to say to 90 % of the studied vegetable material. The cultivation with major formation of esclerotia, originated from the isolation of tomato was the cultivation spinach beet with an average of 33.5 esclerotia, and of equal way this cultivation was predominant to the attack of the mushroom with an average of 45 esclerotes originated from the isolation the cultivation of rice, the cultivation of bean no present infections of the mushroom in none of two evaluated isolations.